Polymer pen lithography - Giam, Louise R. (2012)
We report a low-cost, high-throughput scanning probe lithography method that uses a soft elastomeric tip array, rather than tips mounted on individual cantilevers, to deliver inks to a surface in a “direct write” manner. Polymer pen lithography merges the feature size control of dip-pen nanolithography with the large-area capability of contact printing. Because ink delivery is time and force dependent, features on the nanometer, micrometer, and macroscopic length scales can be formed with the same tip array. Arrays with as many as about 11 million pyramid-shaped pens can be brought into contact with substrates and readily leveled optically to ensure uniform pattern development.